Studi Analisis Potensi PLTMH di Sungai Welang Kecamatan Purwodadi Kabupaten Pasuruan - Mauludina, Nur Ulfa; Ichsan, Yasmin Fakhira; Fadhilah, Millatina (J-Eltrik, 2023)
This research aims to explore the potential utilization of electrical energy from the Welang River through the establishment of a Micro Hydro Power Plant (PLTMH) as a solution to the shortage of electricity supply in isolated areas. The Welang River was chosen due to its highly potential characteristics for development as a renewable energy source. The population around the Welang River has long relied on this natural resource, but its full potential has not been fully utilized. The analysis results show that the Welang River has significant potential, with PLTMH contributing about 0.036% of the electricity needs in Pasuruan Regency. The study involves the analysis of water discharge, river elevation, and water flow characteristics. Nevertheless, routine evaluations are required to ensure the sustainability and availability of electricity from PLTMH in the long term.